Implementation of Strengthening the Profil Pelajar Pancasila in Student Character Development - Iffatul Lailiyah; Umi Azizah; Alfoyatin Mutoharoh; Latifatul Maulidiyah (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
The things that form the background for the formation of the Pancasila student profile are character educators who are starting to erode with time and are increasingly being forgotten. It is in this character education that students of Pancasila are realized who become the profile of the Indonesian nation in the national and international spheres. The Ministry of Education and Culture stated that